Electrophoretic Deposition and Characterization of the Doped BaCeO3 Barrier Layers on a Supporting Ce0.8Sm0.2O1.9 Solid-State Electrolyte - Elena Kalinina; Kirill Shubin; Elena Pikalova (Membranes, 2022)
In this study, the technology of electrophoretic deposition (EPD) micrometer barrier layers based on a BaCe0.8Sm0.19Cu0.1O3 (BCSCuO) protonic conductor on dense carrying Ce0.8Sm0.2O1.9 (SDC) solid-state electrolyte substrates is developed. Methods for creating conductive sublayers on non-conductive SDC substrates under EPD conditions, such as the synthesis of a conductive polypyrrole (PPy) layer and deposition of a layer of finely dispersed platinum from a suspension of its powder in isopropanol, are proposed. The kinetics of disaggregation, disperse composition, electrokinetic potential, and the effect of adding iodine to the BCSCuO suspension on these parameters as factors determining the preparation of stable suspensions and successful EPD processes are explored. Button cells based on a carrying SDC electrolyte of 550 μm in thickness with BCSCuO layers (8–35 μm) on the anode, cathode, and anode/cathode side, and Pt electrodes are electrochemically tested. It was found that the effect of blocking the electronic current in the SDC substrate under OCV conditions was maximal for the cells with barrier layers deposited on the anode side. The technology developed in this study can be used to fabricate solid oxide fuel cells with doped CeO2 electrolyte membranes characterized by mixed ionic–electronic conductivity (MIEC) under reducing atmospheres.